Attracting Investment for Rural Development: Introduction of Organic Agriculture and ESG Principles in Kazakhstan - KUANDYKOVA, Marzhan; AKPANOV, Aidos; TLEUBAYEVA, Santay; BELGIBAYEV, Anuar; MAKHMUDOV, Askar; ATCHABAROVA, Aigul (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).04, 2023)
Today, the market for organic products is one of the most dynamic in the world. The prerequisites for this are the growing consumer demand for food that is environmentally friendly and safe for human health. In Kazakhstan, despite the existing problem, the development of organic production in the agro-food system appears promising and, if implemented in compliance with environmrntal, social and governance (ESG) principles, can be beneficial for the country, which determines the relevance of the study. The purpose of the study is to analyze the possibilities of investment incentives for organic agriculture for the sake of the development of Kazakhstan's rural areas and the implementation of ESG principles. The study employs the following general scientific methods: a) theoretical: analysis of scientific sources; b) empirical: the focused interview method (focus group), an online expert survey; c) mathematical and statistical methods of data analysis; triangulation method. The study concludes that Kazakhstan has considerable potential for the development of organic agriculture. The production of organic products in Kazakhstan is an extremely promising area that can promote the competitiveness of agricultural products, significantly improve the country's image on the world stage, and facilitate the development of market infrastructure and sustainable development of the country as a whole.